(untitled) (Torani Journal of Fisheries and Marine Science, 2024)
Indonesia is one of the largest seafood producing countries in the world, with significant fisheries potential to support national economic growth. This study aim to analyzes the export volume and value trends of Indonesia’s fishery products from 2018 to 2023, focusing on key commodities such as shrimp, tuna, seaweed, crabs, and lobster. The data used includes annual export volume and value for each commodity. The analysis results show that the volume of Indonesia’s fishery exports fluctuated, with a significant increase until 2020 (1,262,830 tons) and a decline in 2021 and 2022, although it remained stable in 2023 (1,221,196 tons). The export value also showed a significant increasing trend, peaking in 2022 at 6,242,085 USD, before decreasing to 5,630,947 USD in 2023. Despite the decline in the last two years, the fishery sector in Indonesia continues to make a significant contribution to the national economy, with key commodities maintaining high competitiveness in the international market. These findings are important for the development of strategies that can boost Indonesia’s fishery exports and strengthen its position as a leading global exporter.